Pengaruh Keagamaan dan Kompetensi Terhadap Kinerja Guru PAI di Madrasah Aliyah Negeri (MAN) Kota Bengkulu - Dianti, Eka; Nurlaili, Nurlaili; Dewi, Desy Eka Citra (UIN Fatmawati Sukarno Bengkulu, 2024)
The aim of this research is (1) to analyze the magnitude of the influence of religious activities on the performance of PAI teachers at Madrasah Aliyah Negeri (MAN) Bengkulu City. (2) Analyzing the magnitude of the influence of competency on the performance of PAI teachers at Madrasah Aliyah Negeri (MAN) Bengkulu City. (3) Analyzing the magnitude of the influence of religion and competence on the performance of PAI teachers at Madrasah Aliyah Negeri (MAN) Bengkulu City. The type of research used in this research is quantitative research, the research instrument used is a questionnaire, the data analysis techniques used are descriptive statistics, basic assumption tests, classical assumption tests, and hypothesis testing using simple linear regression and multiple linear regression, t test and F test. Research results: (1) There is an influence of religious activities on the performance of PAI teachers at Madrasah Aliyah Negeri (MAN) Bengkulu City which is shown at t count (2.053) > t table (5% = 1.70) and a significance level of 0.046 < 0.05. (2) There is an influence of COMPETENCY on the performance of PAI teachers at Madrasah Aliyah Negeri (MAN) Bengkulu City which is shown in t count (2.862) > t table (5% = 1.70) and a significance level of 0.007 < 0.05. (3) There is an influence of religious activities and competence on the performance of PAI teachers at Madrasah Aliyah Negeri (MAN) Bengkulu City which is shown in t count (3.875) > t table (5% = 2.85) and a significance level of 0.032 < 0.05.